IMPORTANCE OF LOCATING STRIKE IN 2D MAGNETOTELLURIC DATA MODELING - Nazli Ismail (Jurnal Natural, 2013)
2D inversion is still believed as the fastest, cheapest, and most reliable method magnetotelluric data interpretation. Traditionally the magnetotelluric data are collected on 2D profile perpendicularly across an assumed geological strike. However there is no guarantee where the chosen strike is exactly or nearly same as true geoelectrical strike. For this purpose, 2D synthetic magnetotelluric impedance data of a simple 2D model were generated along a profile across the model. The data were inverted on various presumed strike in order to study how far the inverted model is deviated when the presumed strike is moved away to the true strike. By the aim, first the data were inverted as measured on 2D profile perpendicularly across true strike in order to see how the inversion works in the ideal case. Thedata were also inverted as measured on 2D profile perpendicularly across an assumed strike. The presumed strike deviated 60 degrees to the true strike was selected as an example of extreme case. The model inverted from the extreme presumed strike data is compared to the actual one. The inversions on determinant and combined TE and TM modes have been done as well for model resolution comparison.